Optimisation of Printing Process Significant Parameter and Level via Simulation on Printing of Synthetic Leather Substrate - Seeni Iburahim, Thajul Mydin; Khirotdin, Rd Khairilhijra (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Synthetic leather materials includes polyurethane (PU), polyvinyl chloride (PVC) and microfiber leather is a low-cost material that performs similarly to actual leather in terms of function and orientation and Ultraviolet (UV) printing ink have been seen used widely to print pattern on synthetic leather substrates. However, some disadvantages were discovered, including an unpleasant odour and several health concerns induced by excessive UV radiation exposure. Therefore, research is required to resolve such issues based on the direct printing technique using eco-solvent ink. In this study, a simulation was conducted via Minitab software to characterise and optimise the significant and level of printing parameters for printing process on synthetic leather substrate. This involvement determines the optimal value for both the significant and level of printing parameters that correlate to the line width and pattern edge response values. Four input parameters were identified including number of pass, printing speed, the height deposition of the printer head and viscosity of the ink. The result obtained shows that only number of pass (6,8, and 10) and printing speed (VSD_2, VSD_3 and VSD_4) are statistically significant with 3-levels of design for printing process on synthetic leather substrate.